Self-compassion and responses to health information in middle-aged and older women: An observational cohort study. (October 2021) - Semenchuk, Brittany N; Boreskie, Kevin F; Hay, Jacqueline L; Miller, Cindy; Duhamel, Todd A; Strachan, Shaelyn M
The aim of this study was to determine whether self-compassion—orientation to care for oneself during challenges—helps people at risk of cardiovascular disease deal with emotional reactions and assist with self-regulating health behaviors. This observational study recruited women ( N = 102) who attended three research visits over 3 weeks to gather information on emotions, intentions, and engagement in health behaviors after women received news they were at risk of cardiovascular disease. Self-compassion negatively associated with emotional responses and associated with intentions and engagement in health behaviors after receiving news of their cardiovascular disease risk. Self-compassion was associated with adaptive lifestyle behaviors.